THE ANALYSIS OF AUTHENTIC ASSESSMENT IMPLEMENTATION USING ANEKDOT RECORD WITH DIVISION OF STUDENTS MODEL IN MAWAR CLUSTER, SEMARANG REGENCY - Kumalasari, Ade; Waluyo, Edi (BELIA: Early Childhood Education Papers, 2019)
Authentic assessment with anecdot note with division of students? model is an assessment model with division into several groups. The implementation of anecdot notes in the Mawar Cluster Semarang Regency is the teacher records all the activities, attitudes, and behaviors of children which are carried out by children every day or that appear suddenly. In implementing anecdot notes, the teacher sometimes only records negative things; as a consequence, the teacher skips positive behavior that can enter anecdot notes sometimes. The purposes of this study are to determine teacher understanding of the implementation of authentic assessment using anecdot notes in the Mawar Cluster Semarang Regency. Then, it is to find out the process of analyzing anecdot records with the division of students model conducted by teachers in the Mawar Cluster Semarang District. This study uses qualitative research methods with the type of descriptive research method percentage. Data are collected using questionnaires and interviews, questionnaires are filled out by each class teacher, while interviews are conducted to the vice-principal of curriculum in the institution. The respondents in the study are 26 teachers taken from the TK Negeri Pembina (Pembina State Kindergarten) Semarang Regency, TK Kartini 01 Karangjati, and Kartini 02 Kindergarten. The results of the analytical study of authentic assessment implementation variables are obtained on average = 45.85, minimum value = 39, the maximum value = 53, the middle value (median) = 45, the frequently occurring value (mode) = 44 and the standard deviation = 2.96. 92.31% of teachers carry out authentic assessments very well, 3.85% of teachers perform authentic assessments very well, and 3.85% of teachers do authentic assessments very well. The results of the interviews are obtained from the results of an authentic assessment analysis process using anecdot record with a division of students model conducted in the Mawar Cluster Semarang Regency following the stages of assessment that is daily assessments, then described in data compilation and summarized into report results of child development. Keywords : Authentic Assessment, Anecdot Notes, Division of Students Model.